The Implementation of Madrasah Aliyah Curriculum: Quality Improvement Management - Pahrudin, Agus; Kuswanto, Cahniyo Wijaya; Leni, Nurhasanah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Curriculum is one element that contributes greatly to realizing the students’ quality and potential development. To face the challenges that will befall the world of education in Indonesia, clarity of the curriculum and its implementation is needed to improve the performance of education which is far behind the developed countries in the world. This study aims to see how to improve the quality of curriculum implementation at Madrasah Aliyah in Bandar Lampung City. The researcher employed the mixed methods with source explanatory design and source triangulation design involving 34 teachers in two madrasahs in Bandar Lampung City. The study revealed that teachers' ability to prepare lesson plans influences their performance in learning. The percentage of effects obtained from MAN 1 Bandar Lampung was 36.6 percent, while the percentage value obtained from MAN 2 Bandar Lampung was 46.4 percent. The results are in line with the theory that the teacher's ability to prepare lesson plans will positively impact the teacher's ability to carry out learning. The results in both schools show that the greater the teacher's ability to prepare lesson plans, the greater the teacher's ability to carry out learning.